Odpowiedzi

2010-01-14T17:35:52+01:00
7x-4=x+2,
7x -x = 2 +4
6x = 6
x = 1
L(1) = 7*1 -4 = 7-4 = 3
P(1) = 1 + 2= 3
L(1) = P(1)

-5x+4=x-8,
-5x -x = -8 -4
-6x = -12
x = (-12) : (-6)
x = 2
L(2) = (-5)*2 + 4 = -10 + 4 = -6
P(2) = 2 -8 = -6
L(2) = P(2)

-2x-7=2x-7,
-2x -2x = -7 +7
-4x = 0
x = 0
L(0) = -1*0 -7 = -7
P(0) = 2*0 -7 = -7

-7x+5=11x+41
-7x -11x = 41 -5
-18x = 36
x = 36 : (-18)
x = -2

L(-2) =(-7)*(-2) + 5 = 14 + 5 = 19
P(-2) = 11*(-2) + 41 = -22 + 41 = 19
L(-2) = P(-2)

36x-14=14x-36
36x -14 x = -36 +14
22 x = -22
x = (-22) : 22
x = -1
L(-1) = 36*(-1) -14 = -36 -14 = -50
P(-1) = 14*(-1) -36 = -14 -36 = -50
L(-1) = P(-1)
Najlepsza Odpowiedź!
2010-01-14T17:51:24+01:00
1) 7x-4=x+2 7x-x=2+4 6x=6 /:6 x=1 spr. (7*1)-4=1+2 3=3
2) -5x+4=x-8 -5x-x=-8-4 -6x=-12 /(-6) x=2 spr. (-5*2)+4=2-8 -6=-6
3)-2x-7=2x-7 -2x-2x=-7+7 4x=0 /:4 x=0 spr.(-2*0)-7=(2*0)-7 0-7=0-7 -7=-7
4)-7x+5=11x+41 -7x-11x=41-5 -18x=36 /:(-18) x=-2
spr.(-7*-2)+5=[11*(-2)]+41 14+5=-22+41 19=19
5)36x-14=14x-36 36x-14x=-36+14 22x=-22 /:22 x=-1
spr. [36*(-1)]-14=[14*(-1)]-36 -36-14=-14-36 -50=-50